2006
DOI: 10.1007/s10578-006-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Studying Cross-cultural Differences in the Development of Infant Temperament: People’s Republic of China, the United States of America, and Spain

Abstract: Investigated early development of temperament across three cultures: People's Republic of China (PRC), United States of America (US), and Spain, utilizing a longitudinal design (assessments at 3, 6, and 9 months of age). Selection of these countries presented an opportunity to conduct Eastern-Western/Individualistic-Collectivistic comparisons. The greatest number of significant differences (i.e., involving more temperament dimensions) was anticipated for the US (Western/Individualistic) and PRC (Eastern/Collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 32 publications
5
65
3
Order By: Relevance
“…Finally, cultural differences in parenting might account for differences in factor structure. First, despite a genetic component of temperament, child rearing fosters temperament characteristics that are in line with the respective cultural values (Kohnstamm, 1989;Gartstein et al, 2006). Second, parents potentially rate their infants' temperament characteristics by referring to culture-specific standards on, e.g., desirability and normativity (Slobodskaya, Gartstein, Nakagawa, & Putnam, 2012).…”
Section: Underlying Temperament Dimensionsmentioning
confidence: 99%
“…Finally, cultural differences in parenting might account for differences in factor structure. First, despite a genetic component of temperament, child rearing fosters temperament characteristics that are in line with the respective cultural values (Kohnstamm, 1989;Gartstein et al, 2006). Second, parents potentially rate their infants' temperament characteristics by referring to culture-specific standards on, e.g., desirability and normativity (Slobodskaya, Gartstein, Nakagawa, & Putnam, 2012).…”
Section: Underlying Temperament Dimensionsmentioning
confidence: 99%
“…Some researchers have argued that temperamental shyness (i.e., inhibition) is more prevalent in East Asian countries compared to the United States, Canada, Western European countries, and Australia (Gartstein et al, 2006 ;Rubin, Hemphill, et al, 2006 ). For example, Rubin, Hemphill, et al (2006) found that Chinese and Korean toddlers exhibited more inhibited behavior in Kagan ' s " Inhibition paradigm " (e.g., Kagan, Reznick, & Snidman, 1988 ) than Australian and Italian toddlers.…”
Section: Prevalence Of S Hyness and S Ocial W Ithdrawalmentioning
confidence: 99%
“…Such collectivistic characteristics are reflected in the way people interact. A higher tendency toward introversion (e.g., more reserved, less outgoing, and less sociable) was consistently found among the Chinese population (Ahadi, Rothbart, & Ye, 1993;Gartstein et al, 2006;McCrae, Costa, & Yik, 1996), and Taiwanese youth also tend to behave modestly or to be shy compared to their western peers (Carducci & Zimbardo, 1995).…”
Section: Introductionmentioning
confidence: 98%